Prehistoric quarries and terranes - Shott, Michael Joseph. (Salt Lake City)
xvi, 279 sayfa
Keywords: “Because of the sheer volume of industrial debris and the limited information it yields, quarries are challenging archaeological subjects. Michael J. Shott tackles this challenge in a study of flakes and preforms from the Modena and Tempiute obsidian quarries of North America's Great Basin. Using new statistical methods combined with experimental controls and mass analysis, Shott extracts detailed information from debris assemblages, and parses them by successive 'stages' of reduction continua. The book also reports the first test of the behavioral ecology field-processing model that treats quarry biface production in continuous terms, and estimates the production efficiency of prehistoric Great Basin knappers. After mapping and interpreting the abundance and distribution of quarry products, Shott concludes by charting future lines of research in the analysis of large toolstone sources. Whatever area of the world and technological traditions they research, lithic analysts will learn much from this book's approach to complex archaeological deposits and their constituent artifacts.“ --